The Balance Between Heterogeneous and Homogeneous Nucleation of Ice Clouds Using CAM5/CARMA. Issue 6 (23rd March 2022) - Maloney, Christopher; Toon, Brian; Bardeen, Charles; Yu, Pengfei; Froyd, Karl; Kay, Jennifer; Woods, Sarah
Abstract: We present a modification to the Community Aerosol and Radiation model for Atmospheres (CARMA) sectional ice microphysical model where we have added interactive nucleation of sulfates and heterogeneous nucleation onto dust in order to create a more comprehensive representation of ice nucleation within the CARMA sectional ice model. The Yu et al. (2019, https://doi.org/10.1029/2018gl080544 ) convective wet removal fix has also been added in order to correctly transport aerosol within the Community Atmosphere Model version 5 (CAM5) and the 3‐mode Modal Aerosols Model (MAM3). In CARMA, the balance of homogeneous and heterogeneous nucleation is controlled by the presence of temperatures below 240 K, supersaturation, and the availability of heterogeneous nuclei. Due to a paucity of dust at altitudes above about 7 km, where temperatures over most of the Earth fall below 240 K, cirrus clouds above 7 km nucleate primarily via homogeneous nucleation on aqueous sulfate aerosols in our simulations. Over mid‐latitudes of the Northern Hemisphere, dust is more common above 7 km during spring through fall, and both heterogeneous nucleation and homogenous freezing occur in our model. Below 7 km heterogeneous nucleation dominates in situ formation of ice. Furthermore, we find an improvement of the representation of in‐cloud ice within mixed phase clouds in CAM5/CARMA when compared to simulations with only homogeneous ice nucleation. Other modes of nucleation such as contact nucleation of liquid cloud droplets or liquid cloud droplet freezing on immersion nuclei, were not directly compared with classical depositional heterogeneous nucleation in this study. Plain Language Summary: The work presented here modified ice nucleation within the Community Aerosol and Radiation model for Atmospheres cirrus model in two ways. The first modification introduced an evolving sulfate aerosol field in place of the current sulfate climatology, while the second modification added depositional heterogeneous nucleation of ice onto dust. This work also adapted a fix to the wet removal of aerosols within convection from a previous study. This fix leads to a better representation of the vertical transport of aerosols within version 5 of the Community Atmosphere Model (CAM5). Simulations show that the addition of heterogeneous nucleation improves dust mass when compared to aircraft observations. Over the mid‐latitudes in the Northern Hemisphere, dust is commonly found above 7 km in altitude and both heterogeneous and homogeneous nucleation occurs over the course of the year. Simulated cirrus ice clouds experience only minor impacts from the added nucleation schemes presented in this work, but our results show that the addition of heterogeneous nucleation improves the representation of in‐cloud ice, especially within mixed phase clouds when compared to simulations without heterogeneous nucleation. Key Points: Interactive aerosols and heterogeneous nucleation are added to the CAM5/CARMA sectional ice model Simulated dust profiles compare better to Particle Analysis by Laser Mass Spectrometry observations as a result of our CAM5/CARMA modifications Mixed phase clouds in the mid‐latitudes are the most impacted by the addition of heterogeneous nucleation in Community Aerosol and Radiation model for Atmospheres (CARMA)